470. The Effects of Arrival Quarantine on Subsequent COVID-19 Testing in a Cohort of Military Basic Trainees. (31st December 2020) - Marcus, Joseph E; Frankel, Dianne; Pawlak, Mary; Casey, Theresa; Enriquez, Erin; Yun, Heather
Abstract: Background: The COVID-19 pandemic has been associated with significant spread in congregate settings and various forms of non-pharmaceutical interventions (NPI) have been implemented to prevent spread. Basic Military Training at Joint Base-San Antonio is the entrance to the US Air Force and has been associated with respiratory outbreaks in the past. A two-week arrival quarantine was implemented in March 2020. Effects on subsequent testing for COVID-19 after an arrival quarantine is unknown. Methods: The first four weekly cohorts of trainees who underwent an arrival quarantine between March 16-April 13 were monitored during their 7 week training for COVID-19 symptoms. Symptoms, medical testing, and days removed from training were collected on every patient with possible COVID-19 symptoms including cough, shortness of breath, or fever. Testing during the two-week arrival quarantine were compared to the subsequent five weeks of training. Nominal variables were compared by chi squared or Fisher's exact test as appropriate. Continuous variables were compared by Mann-Whitney U Test. Results: A total of 2, 573 started training during study period, 89 (3.4%) had symptoms concerning for COVID-19 and were tested. 5 (6%) patients tested positive, all of whom in the arrival quarantine. Compared to patients who completed quarantine (n=29), patients in the arrival quarantine who tested negative for COVID-19 (n=54) were tested more often (26 trainees a week vs. 5.8 later in training, p=< 0.0001), and received more rapid flu tests (74% vs. 38%, p=0.001) and multiplex respiratory PCR (15% vs. 0%, p=0.05). Trainees in quarantine were isolated longer for symptoms than patients who completed quarantine (median 3 vs. 2, p=0.01). There was no difference in presenting symptoms for trainees in quarantine or after quarantine. Conclusion: Arrival quarantine appears to be an effective NPI, which in conjunction with other interventions prevented any COVID-19 transmission after quarantine completion. For those who went through arrival quarantine, there was more intense initial testing and initial longer symptomatic patient isolation, this was balanced by fewer symptomatic patients, less testing, and shorter isolations later in training. Disclosures: All Authors : No reported disclosures